The Relationship Between Husband and Cadre Support With The Compliance of Pregnant Women in Taking Blood-added Tablets at Bangetayu Health Center Semarang City - Hanifa Andisetyana Putri; Elisa Ulfiana; Dewi Andang Prastika; Khoirun Nikmah (Journal of Midwifery Science: Basic and Applied Research, 2022)
Anemia is a condition where the hemoglobin (Hb) level in red blood cells is lower than the standard. Pregnant women are said to be anemic if the Hb content is 11gr/dl. The prevalence rate of anemia in pregnant women in Indonesia is 48.9%, in Central Java in 2018 it was 57.1%, while in Semarang City in 2021 it reached 15.4%, in Bangetayu Health Center it was 19.93%. Anemia in pregnant women can increase the risk of premature birth, maternal and child mortality, and infectious diseases. Government efforts require pregnant women to take a minimum of 90 tablets during pregnancy. One of the factors causing high anemia in pregnant women is the low compliance of pregnant women in taking blood supplement tablets. Support from husbands and cadres is needed to increase compliance when taking blood tablets. The purpose of this study was to determine the relationship between husband and cadre support with the compliance of pregnant women in taking blood supplement tablets at Bangetayu Health Center, Semarang City.This study used quantitative research methods with a cross sectional approach. The population in this study were all pregnant women in the third trimester in May in the Bangetayu Health Center working area of Semarang City, totaling 39 respondents. Sampling with simple random sampling technique. Data analysis using ch square test.The results showed that there was a relationship between husband support (p value 0.00) and cadres (p value 0.00) with the compliance of pregnant women in taking blood supplement tablets at Bangetayu Health Center, Semarang City. The existence of this study is expected that health workers can involve husbands and cadres to supervise pregnant women in taking blood tablets.